Banks and Social Responsibility as a Measure of Success - Haza Barrantes, Antonio De la (2010)
Corporate social responsibility can be defined as the harmonious management between economic, social and environmental areas; and at the same time, it recognizes the interests of the public with which it is related: shareholders, employees, community, suppliers and customers. Based on this, the possibility of considering CSR as a tool for measuring success in the business sector is considered. Thus, this article seeks to develop the RS policy tools in a banking company. In the first place, it highlights that the SR must be linked to good corporate governance policies through its main tool: human capital. For this reason, the "balanced scorecard" or BSC technique is mentioned in which it consists of measuring the performance and well-being of all employees and then defining the company's new objectives. The aforementioned technique consists of carrying out a strategic plan to then carry out the personnel performance review and finally make the monthly monitoring of the BSC for each unit. The second mechanism is the use of knowledge and financial experience to raise the level of banking in our country. However, the author emphasizes highlighting the pragmatic side of the situation mentioning the examples of the banks Scotiabank, BCP and the BBVA Continental Group. Finally, the author emphasizes the power that the client owns given that he has the possibility of punishing or rewarding the entrepreneur who assumes minimum or maximum standards of social responsibility.